Dual Functions of the Steroid Hormone Receptor Coactivator 3 in Modulating Resistance to Thyroid Hormone - Ying, Hao (American Society for Microbiology, 2005)
Mutations of the thyroid hormone receptor β (TRβ) gene cause resistance to thyroid hormone (RTH). RTH is characterized by increased serum thyroid hormone associated with nonsuppressible thyroid-stimulating hormone (TSH) and impaired growth. It is unclear how the actions of TRβ mutants are modulated in vivo to affect the manifestation of RTH. Using a mouse model of RTH that harbors a knockin mutation of the TRβ gene (TRβPV mouse), we investigated the effect of the steroid hormone receptor coactivator 3 (SRC-3) on RTH. In TRβPV mice deficient in SRC-3, dysfunction of the pituitary-thyroid axis and hypercholesterolemia was lessened, but growth impairment of RTH was worsened. The lessened dysfunction of the pituitary-thyroid axis was attributed to a significant decrease in growth of the thyroid and pituitary. Serum insulin-like growth factor 1 (IGF-1) was further reduced in TRβPV mice deficient in SRC-3. This effect led to reduced signaling of the IGF-1/phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway that is known to mediate cell growth and proliferation. Thus, SRC-3 modulates RTH by at least two mechanisms, one via its role as a receptor coregulator and the other via its growth regulatory role through the IGF-1/PI3K/AKT/mTOR signaling.